From Floating to Monetary Union: The Economic Distance between Exchange Rate Regimes - Eduard Hochreiter; Pierre Siklos (SUERF - The European Money and Finance Forum, 2004)
The successful start of Economic and Monetary Union in Europe has prompted more research into the issue of exchange rate regimes and if there were any lessons to be drawn from the European experiment for other regions in the world. We review the relevant issues from an Optimum Currency Area perspective. The focus on issues relating to the suitability of switching to a common currency based on notions of economic distance and the correlation of aggregate economic shocks. The empirical evidence presented in this paper shows that the cost of monetary union declined substantially in some target countries while it appears to have risen in others. This leads to some interesting policy implications also for the new EU members.
Keywords: E30; F30; 330; Exchange rate regimes; Monetary Union; Economic Distance; Wechselkurssystem; Flexibler Wechselkurs; Optimaler Währungsraum; Eurozone; Schock; Schätzung